Catalytic combustion of methyl butanoate over HZSM-5 zeolites. Issue 18 (17th February 2021) - Zhai, Yitong; Feng, Beibei; Meng, Qinghui; Ao, Chengcheng; Qian, Siyu; Zhang, Lidong
Abstract : A catalytic combustion mechanism of methyl butanoate over HZSM-5 was proposed and validated by experimental data and theoretical calculations. Abstract : Catalytic combustion technology is an exciting prospect for the removal of pollutants, especially in the field of transportation. Applying zeolites in fuel combustion has gained increasing importance in heterogeneous catalysis arising from their properties such as economical practicability and high activity. However, compared with the extensively investigated homogeneous combustion, few studies have been reported to explore the catalytic combustion of large-molecule fuels, especially for the catalytic combustion of biodiesel surrogate fuels. The purpose of this feature article is to describe the catalytic combustion of methyl butanoate (one of the biodiesel surrogate fuels) over unmodified HZSM-5 zeolites with a particular focus on the catalytic reaction mechanism. Experiments and theoretical calculations were considered here to help explain the proposed catalytic mechanism. This paper can provide new insights into the catalytic mechanism of biodiesel fuels that will guide the improvement of combustion efficiency in internal combustion engines and in the control of pollutant emissions.